REKONSTRUKSI TRANSPARANSI MANAJERIAL: UPAYA SINKRONISASI VISI KEPALA SEKOLAH DENGAN AKUNTABILITAS DALAM MBS - Gede Agung, Anak Agung; Chindytia; Ni Made Ayu Mas Candra Dewi; Ayu Nyoman Trisya Dewi; Putu Jasmine Liani Martayunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by a managerial paradox at SD No 5 Kapal, where strong visionary and participative leadership had not been accompanied by adequate administrative transparency. The study aimed to analyze and formulate transparency reconstruction strategies to synchronize the principal's vision with accountability within the School-Based Management (SBM) framework. Using a qualitative case study approach, data were collected through structured observation and documentation studies, then analyzed using the Miles and Huberman model. The results show that visionary leadership and participative decision-making are in the